Postpartum Depression and Self-Compassion in Working New Mothers: A Phenomenology Study - Mayenrisari Arifin A. Pasinringi; Endang Retno Surjaningrum; Primatia Yogi Wulandari (Future Science, 2024)
Some employed new mothers find that the experience of childbirth and the postpartum period can enhance their mental well-being and happiness. Nevertheless, not all employed new mothers perceive positive outcomes during this time. The aim of this study is to investigate the risk of postpartum depression and its connection with self-compassion among employed new mothers. The research method used is a phenomenology approach with seven new working mothers who have babies aged twelve months as participants. Data collection was conducted through interviews and filled of The Edinburgh Postnatal Depression Scale (EPDS) to determine the level of postpartum depression experienced. The results of this study describe the experience of self-compassion in working new mothers who experience postpartum depression, which is related to the mental process that occurs within the individual to focus on being wise and kind to oneself with all the shortcomings experienced during the postpartum phase. In reality, working new mothers are less able to respond sensitively to their babies, difficult to regulate themselves in mother-baby interactions, and adopt a caring parenting approach, which has an impact on the occurrence of postpartum depression. The contribution of this study is to find efforts to prevent depression in postpartum mothers. In addition, it is also how relevant agencies consider several policies that support the mental health of postpartum working new mothers.